Offering soybean molasses adsorbed to agricultural by‐products improved lactation performance through modulating plasma metabolic enzyme pool of lactating cows. Issue 12 (13th October 2021) - Chen, Liang; Mi, Hui; Li, Bin; Liu, Yong; Zhou, Chuanshe; Ren, Ao; Tan, Zhiliang; Kong, Zhiwei; Fang, Rejun; Zhang, Ge
Abstract: Background: Agricultural by‐products, such as corncob powder (CRP), wheat bran (WB), rice husk (RH), defatted bran (DB), and soybean hulls (SH), were widely used as ruminant feed. However, the combination effect of soybean molasses mixed with agricultural by‐products on cow lactating performance remains poorly understood. Methods: In vitro fermentation simulation technique was used to select the high ruminal fermentation performance of agricultural by‐products mixed with soybean molasses. The selected mixtures were conducted to further explore the feeding effect on milk performance and blood metabolic enzyme on lactating dairy cows. Results: In in vitro simulation, it was confirmed that SH‐SM showed better fermentation performance (including higher maximum gas production, acetate, propionate, and total VFA, but less initial fractional rate of degradation) than other four molasses‐adsorbents, while WB‐SM had the greatest DM and NDF disappearance and NH3‐N and butyrate concentrations among substrates. After the simulation selection, we performed the feed experiment with SH‐SM and WB‐SM compared to the control. For lactating performance, higher ( p < .01) milk fat and total milk solid content were observed in WB‐SM, and a tendency improvement of milk protein content ( p < .01) was observed in both of the cows fed with WB‐SM and SH‐SM. Among lactating periods, the blood glutamic‐pyruvic transaminase, α‐amylase, and lactate dehydrogenase which associated with amino acid metabolism and carbohydrate metabolism were improved in lactating dairy cows fed with WB‐SM and SH‐SM. Conclusion: Dietary agricultural by‐products (like wheat bran and soybean hulls) mixed with soybean molasses enhance the lactating performance of dairy cows by improving the host metabolism process of amino acids and carbohydrates. The mixed strategy for agricultural by‐products shows another strong evidence for the resource reuse on dairy industry and reducing the by‐product pollution. Abstract : Dietary agricultural by‐products (like wheat bran and soybean hulls) mixed with soybean molasses enhances the lactating performance of dairy cows by improving the host metabolism process of amino acids and carbohydrates. The mixed strategy for agricultural by‐products shows another strong evidence for the resource reuse on dairy industry and reducing the by‐product pollution.